Photonic tools for evaluating the growth of diatom colonies during long-term batch cultivation - Cvjetinovic, J; Bedoshvili, YD; Nozdriukhin, DV; Salimon, AI; Korsunsky, AM; Gorin, DA (IOP Publishing, 2022)
Diatoms are unicellular photosynthetic microalgae with a nanostructured silica cell wall – frustule. Diatoms, considered one of the most abundant and ecologically important phytoplankton groups, can also be easily grown in the laboratory and used for different applications. With long-term cultivation, it is essential to monitor their growth properly; therefore, we proposed new, fast and easy-to-use methods based on the absorption and fluorescence of diatom chromophores. The average radiant efficiency of diatom culture Achnanthidium sibiricum obtained using the IVIS SpectrumCT In vivo Imaging system increased up to 45 days of cultivation, after which we observed steady decrease. The highest photoacoustic signal of diatoms mixed with an agarose gel excited by a 532 nm laser was also recorded after 45 days of cultivation. The results obtained are in good agreement with the obtained spectra during the 100-day cultivation period. Thus, photonic methods have proven to be effective for monitoring the growth of diatoms during long-term cultivation, expanding the possibilities of growing and collecting diatoms for various purposes.